Faktor-faktor Yang Melatarbelakangi Persepsi Penderita Terhadap Stigma Penyakit Kusta - Soedarjatmi, Soedarjatmi; Istiarti, Tinuk; Widagdo, Laksmono (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2009)
Background: By the year of 2006, there were 4.171 registered leprosy cases in Central Java, 1.989 of them on going treatment, 163 were children and 241 of people deformed due to leprosy. Lack of knowledge on leprosy cause negative perception toward this disease, so willincrease stigma in the community. This study aims to describe the patients’ perception to leprosy disease.Method: This study was a qualitative case study, involved 8 patients selected from leprosy cases with the criteria of on going treatment in Tugurejo Hospital Semarang. In-depth interview was conducted to obtain details answers from respondents.Result: Respondents perceived that leprosy was an infectious disease and it was possible to be infected to other people easily, especially to those who careless in performing healthy behavior. Most of respondents were lack of knowledge of the disease transmission. They perceived that leprosy is a dangerous disease and lead to death or deformities. Positivebehaviors were depicted as a good self care, regular treatment, and socialization whereas negative behaviors were described as in-complying treatment, being isolated and giving up of hopes. All respondents covering their disease and limit their socialization in order to avoid stigmatization.Keyword : Perception, Stigmatization, Leprosy